2007
DOI: 10.1055/s-2007-988367
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-31 mediates MAP kinase and STAT1/3 activation in intestinal epithelial cells and its expression is up-regulated in inflammatory bowel disease

Abstract: Background/aim: Interleukin 31 (IL31), primarily expressed in activated lymphocytes, signals through a heterodimeric receptor complex consisting of the IL31 receptor alpha (IL31Ra) and the oncostatin M receptor (OSMR). The aim of this study was to analyse IL31 receptor expression, signal transduction, and specific biological functions of this cytokine system in intestinal inflammation. Methods: Expression studies were performed by RT-PCR, quantitative PCR, western blotting, and immunohistochemistry. Signal tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…14 In addition, Dambacher et al also demonstrated that IL-31 might mediate ERK-1,2, Akt, STAT-1 and STAT-3 activation in human intestine epithelial cells. 17 In concurrence with these recent findings, we demonstrated the activation of ERK1, JNK1,2 and p38 MAPK signalling molecules in IL-31-stimulated human bronchial epithelial cells (Fig. 5).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…14 In addition, Dambacher et al also demonstrated that IL-31 might mediate ERK-1,2, Akt, STAT-1 and STAT-3 activation in human intestine epithelial cells. 17 In concurrence with these recent findings, we demonstrated the activation of ERK1, JNK1,2 and p38 MAPK signalling molecules in IL-31-stimulated human bronchial epithelial cells (Fig. 5).…”
Section: Discussionsupporting
confidence: 91%
“…The expression of IL‐31RA and OSMR on human epidermal keratinocytes and the number of IL‐31‐expressing, skin‐infiltrating Th2 and CD45RO + (memory) cutaneous lymphocyte antigen (CLA) + T cells in atopic dermatitis patients was higher than in normal subjects 11 . Interleukin‐31 heterodimeric receptors are also present in many tissues including testis, brain, bone marrow, thymus, skin and intestine 10,12 , 15–17 . Target cells expressing IL‐31RA for IL‐31 in these tissues include activated monocytes, macrophages, myeloid progenitor cells, keratinocytes, eosinophils and epithelial cells 10–12,17 , 18 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression of IL-31Ra and OSMRß mRNA can be induced in activated monocytes, while their expression is constitutive in skin, testis and thymus, arguing that these organs are probably responsive to IL-31 (1,9,10). IL-3 IRA and OSMRß are also found co-expressed in a subset of neurons of murine and human dorsal root ganglia (9,11 ), which represents the site where the soma of cutaneous sensory neurons are located, while their sensory fibres protrude directly into the skin.…”
Section: Il-31 Expression By Inflammatory Cells Is Preferentially Elementioning
confidence: 99%